(untitled) (Journal of Asian Development Studies, 2025)
This study investigates the ecological and socioeconomic significance of wild olive (Olea ferruginea) within Murree, Kahuta, and Kotli Sattian National Park. A comprehensive field survey was conducted using the fixed area plot method and quadrate sampling. Results showed considerable variability in tree distribution, with the number of trees per site ranging from 1 to 99 and a mean of 50.49 trees. The high standard deviation (29.16) and variance (850.25) indicated moderate clustering in certain areas. Tree ages ranged from 7 to 10 years (average: 9.29), with 47.5% of trees being 10 years old and only 3% being 7 years old, suggesting limited recent regeneration. Height distribution ranged from 6 to 14 feet (average: 9.13 feet), with most trees falling between 8–10 feet. Diameter at breast height ranged from 4 to 58 cm, with over 80% representing medium-sized trees, while larger specimens were scarce. Standard deviations and variance in growth patterns point to potential environmental or genetic influences. The study highlights a moderately healthy population with signs of regeneration; however, the low proportion of younger and larger trees emphasises the need for targeted conservation measures to support sustainable population dynamics and long-term ecological stability of the wild olive in the park.